Implementasi Plts 50 Wp Untuk Penerangan Jalan Di Kelurahan Manggar Kota Balikpapan - Andi Sri Irtawaty; Maria Ulfah; Armin Armin; Hadiyanto Hadiyanto (Asosiasi Dosen Akuntansi Indonesia, 2022)
Street lamp lighting (SLL) is a complementary element of the street that serves to illuminate the environment around the street, so that road users will feel safe and comfortable. Based on the PkM team survey, RT 100 Manggar Village does not yet have a SLL. Therefore, the PkM team has designed 1 unit of Solar Power Plant (PLTS) with a capacity of 50 wp in the RT with 5 point DC lamp loads on the main road and 1 point placed in a resident's house, as well as placing the panel boxes. The main components of PLTS 50 wp include 50 wp solar panels, 35 ampere controllers, 35 Ah VRLA batteries, fiber cables, 3 watt DC lights, and fittings. The results of the battery endurance test after the solar panel is charged for 5 hours (when the sun is hot), the PLTS is able to turn on 6 light points (3 watts) for 46 hours. This proves that the PLTS is very efficient and suitable to be implemented as a source of PJU electrical energy in Manggar Village, Balikpapan City